Resistance Exercise and Art Therapy on Body Image in Breast Cancer: A Scoping Review - Corrie J. Effa; Naomi D. Dolgoy; Margaret L. McNeely (Mary Ann Liebert, 2020)
Background: Treatments for breast cancer are invasive, causing visible changes such as loss of the breast, body weight change, and hair loss. These changes in conjunction with the pressure for women to conform to societal beauty standards may lead to body image disturbance in breast cancer survivors (BCS). The aims of this scoping review were to explore the nature, characteristics, and extent of the literature examining resistance exercise or art therapy on body image in BCS; and examine how body image is defined and measured across the studies. Methods: We searched the literature up to January 2020, which included conducting electronic searches of three major databases and checking references of screened articles. Results: Ninety-three articles were identified, 28 underwent full-text screening, with 8 studies eligible for inclusion in the review. Five randomized control trials, one hybrid effectiveness-implementation trial, and two single group studies were found. All studies showed significant within-group difference in body image scores, with two studies showing a between-group difference in favor of resistance exercise. No studies were found combining resistance exercise and art therapy. None of the studies defined the aspect of body image they wished to measure, and only one used theory to inform their research. Discussion: Preliminary evidence supports the benefit of resistance exercise and art therapy as single interventions to improve body image perception among BCS. Findings suggest the need for closer attention to the delivery format of interventions. Future research is needed that is theory-informed, with a clear definition of the aspect of body image of interest, and with body image as the primary outcome.